2020
DOI: 10.5194/egusphere-egu2020-12738
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cyclogenesis and density currents in the Middle East and the associated dust activity in September 2015

Abstract: <p>The first 10 days of September 2015 were marked by an intense dust activity over the Middle East and the Arabian Peninsula. This study examines the atmospheric conditions at the origin of the large dust storms during this period. We particularly investigate the atmospheric dynamics leading to the development of a large dry cyclone over Iraq on 31 August 2015 which in turn generated an intense dust storm that affected most of the countries around the Arabian Gulf and lasted for 5 days. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The Middle East is a major contributor to global dust emissions (15%–20% of the total), affecting the regional climate, human health, terrestrial and marine ecosystems (Huneeus et al., 2011; Kok et al., 2021; Zender et al., 2003). Several active deserts are located in the region such as the Egyptian and Nubian deserts in the northeastern Sahara; the Rub‐Al Khali, An Nafud and Al Dahna deserts in the Arabian Peninsula; the Negev desert in Israel; the Syrian‐Iraqi desert; the alluvial flood plains in Mesopotamia; the Dasht‐e Kavir and Dasht‐e Lut deserts in Iran as well as the desiccated, ephemeral or dried‐up lakes like Urmia, Jazmurian and Hamouns in Iran (Cao et al., 2015; Francis, Alshamsi, et al., 2019; Francis, Chaboureau, et al., 2021; Francis, Eayrs, et al., 2019; Ginoux et al., 2012; Kaskaoutis et al., 2016). The regional dust activity is highly sensitive to weather conditions (Bodenheimer et al., 2018; Hermida et al., 2018; Nabavi et al., 2016; Shaheen et al., 2021) and climate perturbations (Hemming et al., 2010; Hoerling et al., 2012).…”
Section: Historical Greenhouse Gas Emissions and Pollutionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Middle East is a major contributor to global dust emissions (15%–20% of the total), affecting the regional climate, human health, terrestrial and marine ecosystems (Huneeus et al., 2011; Kok et al., 2021; Zender et al., 2003). Several active deserts are located in the region such as the Egyptian and Nubian deserts in the northeastern Sahara; the Rub‐Al Khali, An Nafud and Al Dahna deserts in the Arabian Peninsula; the Negev desert in Israel; the Syrian‐Iraqi desert; the alluvial flood plains in Mesopotamia; the Dasht‐e Kavir and Dasht‐e Lut deserts in Iran as well as the desiccated, ephemeral or dried‐up lakes like Urmia, Jazmurian and Hamouns in Iran (Cao et al., 2015; Francis, Alshamsi, et al., 2019; Francis, Chaboureau, et al., 2021; Francis, Eayrs, et al., 2019; Ginoux et al., 2012; Kaskaoutis et al., 2016). The regional dust activity is highly sensitive to weather conditions (Bodenheimer et al., 2018; Hermida et al., 2018; Nabavi et al., 2016; Shaheen et al., 2021) and climate perturbations (Hemming et al., 2010; Hoerling et al., 2012).…”
Section: Historical Greenhouse Gas Emissions and Pollutionmentioning
confidence: 99%
“…Despite the observed decrease in precipitation totals, for some Mediterranean regions, a paradoxical increase of extreme rainfall magnitude or in the number of heavy precipitation days is evident (Alpert et al., 2002; Founda et al., 2013). Particularly for the Middle East, extreme precipitation events can be the result of tropical‐extratropical interactions, for example, Active Red Sea Troughs (De Vries et al., 2013) and cut‐off lows and highs from mid‐latitudes (Francis, Alshamsi, et al., 2019) associated with changes in the polar jet circulation (Francis, Eayrs, et al., 2019; Francis & Vavrus, 2012; Francis et al., 2018; J. Liu et al., 2021). Stratospheric potential vorticity streamers, as indicators of Rossby wave breaking, combined with intense moisture transport, can contribute substantially to this type of extreme event in the region (De Vries, 2021; De Vries et al., 2018).…”
Section: Past and Present State Of The Climatementioning
confidence: 99%
See 1 more Smart Citation
“…AEROIASI uses the hyperspectral measurements of IASI to derive vertically resolved horizontal fields of the aerosol extinction coefficient at 10 μm for cloud-free conditions. Previous studies using AEROIASI observations of the 3D distribution of dust were focused on East Asia (Cuesta et al, 2015) and the Middle East (Francis et al, 2019). For these studies, remarkable agreement between AEROIASI and CALIOP was found for several transects of vertical profiles of the major dust plumes.…”
Section: Introductionmentioning
confidence: 79%
“…In order to visualize the spatial structure and evolution of the TCs, visible satellite images from the Moderate Resolution Imaging Spectroradiometer (MODIS; Kaufman et al., 1997, 2002) instrument onboard the National Aeronautic and Space Administration's (NASA's) Terra and Aqua satellites are extracted from NASA's WorldView website (https://worldview.earthdata.nasa.gov/). Insight into the vertical extent of the clouds and potential dust lifting triggered by the storms is gained through the inspection of false‐color red‐green‐blue (RGB; Banks et al., 2019; Francis et al., 2019; Francis, Fonseca, Nelli, et al., 2022) satellite images from the Spinning Enhanced Visible and Infrared Imager (SEVIRI; Schmetz et al., 2002) instrument onboard the Meteosat Second Generation spacecraft. RGB images are available every 15 min at a 0.05° × 0.05° (∼5.6 km) resolution over the domain 60°S–60°N and 60°W–60°E.…”
Section: Methodology and Datasetsmentioning
confidence: 99%